On establishing an analytical power capture limit for self-reacting point absorber wave energy converters based on dynamic response. (15th October 2018) - Bubbar, K.; Buckham, B.
Highlights: Proposed a new analytical power capture bound for SRPAs based on dynamic response. Proposed a new constraint equation relating the optimal float to spar impedance. Numerically demonstrated how the bound can be approached. Introduced inerters to wave energy community to implement optimal geometry control. Proposed a new condition for null power capture of SRPAs based on geometry control. Abstract: To be a competitive supply of renewable energy, the power capture performance of ocean wave energy converters must improve. This requires that wave energy converter designers identify and invest resources to develop devices that exhibit a strong Technology Performance Level early in the development process. We contend that completing this identification process at the conceptual design stage requires a generalized method to establish the power capture upper bound for any given wave energy converter architecture. This upper bound must reflect simultaneous implementation of both optimal geometry control and power take-off force control – components known to be essential to optimizing performance but difficult to envision for complex WEC architectures. In this work, we develop and demonstrate a procedure, built on the mechanical circuit framework, to identify this upper bound for a self-reacting point absorber with an inertial modulation mechanism performing the geometry control. We illustrate how the analytical procedure generates generic design guidance, required to achieve the bound, without committing to a specific technology. We follow by formally introducing a new technology into the wave energy community, the inerter, capable of implementing the design guidance to enact the required geometry control. Finally, we apply the analytics within a numerical case study of a previously published wave energy converter configuration, and compare the power capture production of that device to one with equivalent hydrodynamics, but with the new geometry control feature set suggested by the new analytical procedure. Our analysis reveals the potential for a ten-fold increase in power capture even under stringent relative displacement constraints.